AB0464 Comparative efficacy of infliximab in patients with rheumatoid arthritis (RA) depending on a total dose (quantity of infusions). (23rd January 2014) - Aronova, E.; Lukina, G.; Sigidin, Y.; Smirnov, A.; Alexandrova, E.; Novikov, A.; Nasonov, E.
Abstract : Objectives: To estimate efficacy of infliximab (INF) in patients (pts) with RA depending on a total dose (quantity of infusions) of this biologic. Methods: The cohort of 135 pts with active RA despite methotrexate therapy (114 women, mean age 48 years, mean disease duration 4 years, RF-positive 75, 6%, mean CRP 18, 1 mg/L, mean HAQ 1, 38) treated in one center with INF (3 mg/kg intravenously at weeks 0, 2, 6 and every 8 weeks thereafter) have been divided into three groups: 1. pts who received not more than 4 INF infusions (N=63); 2. pts who received 5-7 INF infusions (N=31); 3. pts who received more than 7 INF infusions (N=41). DAS28 >5, 1 in the 1-st group was registered in 69% of pts, in the 2-nd group in 86, 6%, in the 3-rd group in 62, 1%. In other aspects both groups were comparable. Results of treatment were assessed by EULAR criteria at weeks 14, 22, and 54. The primary endpoint was the remission rate by the 54-th week. Results: By the 54-th week significant decrease of RA activity was achieved in all groups but DAS28 in 1-st group was significantly higher than in other groups (4, 4 vs 3, 2 in the others; p<0, 05). The remission rate by this time point was 28, 6% in the 2-nd group, 23, 1% in 3-rd group and only 18, 2% in the 1-st group (p<0, 05). It is noteworthy that by the end of the study in the 1-st group there were 36, 4% of pts with high activity; in the 2-nd group, none; in the 3-rd group, 3, 8%. In all groups radiological progression was noted by the 54-th week but among pts who received not more than 4 INF infusions this progression was significantly more pronounced than in other groups. Conclusions: The therapeutic effect of INF was more pronounced in pts who received "middle" doses of infliximab (5-7 infusions) and the full annual course of INF as compared with pts having received low total dose of INF. It refers both to the higher remission rate and to the slowing of radiological progression. Disclosure of Interest: None Declared